Application of a lattice Boltzmann method combined with a Smagorinsky turbulence model to spatially resolved heat flux inside a refrigerated vehicle. (15th November 2018) - Gaedtke, Maximilian; Wachter, Simon; Rädle, Matthias; Nirschl, Hermann; Krause, Mathias J.
Abstract: In this work the simulation of velocity and temperature distributions inside a refrigerated vehicle is evaluated. For this purpose a 3D double distribution lattice Boltzmann method (LBM) with the Bhatnagar–Gross–Krook (BGK) collision operator is coupled by the buoyancy force calculated with the Boussinesq approximation. This LBM is extended by a Smagorinsky subgrid method, which numerically stabilizes the BGK scheme for low resolutions and high Reynolds and Rayleigh numbers. Besides validation against the two benchmark cases porous plate and natural convection in a square cavity evaluated at resolutions of y + ≈ 2 for Ra numbers between 10 3 and 10 10, the method and its implementation are tested via comparison with experimental data for a refrigerated vehicle at R e ≈ 53 000 . The aim of the investigation is to provide a deeper understanding of the refrigerated vehicle's insulation processes including its thermal performance under turbulent flow conditions. Therefore, we extend this method by the half lattice division scheme for conjugate heat transfer to simulate in the geometry of a refrigerated vehicle including its insulation walls. This newly developed method combination enables us to accurately predict velocity and temperature distributions inside the cooled loading area, while spatially resolving the heat flux through the insulation walls. We simulate the time dependent heating process of the open door test and validate against measurements at four characteristic velocity and 13 temperature positions in the truck.